Electrocution in a Sloth (Choloepus didactylus) - Clinical and Surgical Approach - Almeida, Débora da Vera Cruz; Lopes, Cinthia Távora de Albuquerque; Matos, Paulo Cesar Magalhães; Pereira Júnior, José Jones; Imbeloni, Aline Amaral; Domingues, Sheyla Farhayldes Souza (Acta Scientiae Veterinariae, 2022)
Background: High voltage electric shock causes serious injury to the body, which can lead to a fatal condition. Sloths are commonly the target of this type of accident and factors such as the degree of tissue impairment and late medical care can contribute to the death of the animal or the indication of euthanasia. In this way, the present This study aims to describe the treatment strategies in Choloepus didactylus victim of high voltage electrocution. Case: A female sloth weighing 6.15 kg was treated at the Wild Animals Sector of the Veterinary Hospital (SAS-HV) of the Federal University of Pará (UFPA) victim of high voltage electric shock with burn on the right side, stomatitis, glossitis, lesions extensive and bullous lesions in the thoracic and pelvic limbs, in addition to an open fracture in the radioulnar joint of the left limb with signs of necrosis. After patient stabilization (fluid therapy, antibiotic therapy, pain control, cleaning and wound dressing), the patient was admitted to the hospital. The main treatment strategies adopted were surgery, drug therapy, food and occupational therapy. The day after the patient's arrival, the amputation of the left thoracic limb was performed. On the third day of hospitalization, the right thoracic and pelvic limbs were also amputated, and on the tenth day, debridement of the right lateral face was performed. As for drug therapy, the following drugs were used postoperatively: ceftriaxone (40 mg/kg, BID, for 47 days), dexamethasone (0.5 mg/kg, BID, for 4 days), silymarin (15 mg/kg, BID, for 30 days), morphine (0.4 mg/kg, BID, for 14 days; 0.8 mg/kg, SID, for 22 days) and dressing wounds on the lateral face and surgical stumps with ointment based on of collagenase with chloramphenicol. In food management, the animal had good acceptance of a mixture of fruits, vegetables and animal protein in a pasty presentation. The treatment by occupational therapy included basic care such as exercising, sunbathing, and desensitizing the surgical stumps (massage therapy). In conclusion, after five months, the therapeutic protocol implemented resulted in the clinical improvement of the animal, as it allowed the complete healing of the lesions on the face and surgical stumps. In addition, the care taken with the surgical stumps allowed the animal to use them as support for its locomotion. Discussion: Amputation and debridement surgeries were effective in treating electrocuted patients and should be considered when tissue is compromised, which justifies the surgical protocol adopted in this study. They were based on reports in humans, since in wild animals, although many are victims of this type of trauma, little is known about the appropriate therapeutic approach for each species. Surgical interventions associated with the antibiotic ceftriaxone were efficient for controlling the infection, since this antibiotic has a broad spectrum of activity, being used mainly in skin and soft tissue and/or bone infections, which justified its use in that patient. As for nutritional therapy, supplementation with animal protein may have contributed to the clinical improvement of the animal, since they are excellent components for tissue recovery in patients who suffered losses from burns caused by electric shocks. Stump desensitization is indicated as a treatment for neuropathic pain in amputees, and in the present study, it was essential for the animal to use the limb for locomotion. The exercises in a grassy area associated with sunbathing added as a stimulus to the patient's movement. Keywords: two-toed sloth, amputation, nutrition, rehabilitation. Título: Eletrocussão em Preguiça-real (Choloepus didactylus) - abordagem clínica e cirúrgica Descritores: preguiça-de-dois-dedos, amputação, nutrição, reabilitação.